Anticipating sea‐level rise and human migration: A review of empirical evidence and avenues for future research. (12th November 2021) - Duijndam, Sem J.; Botzen, Wouter J. W.; Hagedoorn, Liselotte C.; Aerts, Jeroen C. J. H.
Abstract: Sea‐level rise (SLR) threatens millions of people living in coastal areas through permanent inundation and other SLR‐related hazards. Migration is one way for people to adapt to these coastal changes, but presents an enormous policy challenge given the number of people affected. Knowledge about the relationship between SLR‐related hazards and migration is therefore important to allow for anticipatory policymaking. In recent years, an increasing number of empirical studies have investigated, using survey or census data, how SLR‐related hazards including flooding, salinization, and erosion together with non‐environmental factors influence migration behavior. In this article, we provide a systematic literature review of this empirical work. Our review findings indicate that flooding is not necessarily associated with increased migration. Severe flood events even tend to decrease long‐term migration in developing countries, although more research is needed to better understand the underpinnings of this finding. Salinization and erosion do generally lead to migration, but the number of studies is sparse. Several non‐environmental factors including wealth and place attachment influence migration alongside SLR‐related hazards. Based on the review, we propose a research agenda by outlining knowledge gaps and promising avenues for future research on this topic. Promising research avenues include using behavioral experiments to investigate migration behavior under future SLR scenarios, studying migration among other adaptation strategies, and complementing empirical research with dynamic migration modeling. We conclude that more empirical research on the SLR‐migration nexus is needed to properly understand and anticipate the complex dynamics of migration under SLR, and to design adequate policy responses. This article is categorized under: Climate Economics < Aggregation Techniques for Impacts and Mitigation Costs Vulnerability and Adaptation to Climate Change < Learning from Cases and Analogies Assessing Impacts of Climate Change < Evaluating Future Impacts of Climate Change Abstract : Sea‐level rise (SLR) threatens millions of people living in coastal areas. Migration is one way for people to adapt to SLR‐related hazards, with major implications for people and policy. A more comprehensive understanding of migration dynamics under SLR is therefore vital. Photo: Flood event in Jakarta, Indonesia, 2017. Photo source: World Meteorological Organization on Flickr https://tinyurl.com/8azc3vnr